CD36-mediated ferroptosis dampens intratumoral CD8(+) T-cell effector function and impairs their antitumor ability - Ma, Xingzhe (Cell Metab, 2021)
Understanding the mechanisms underlying how T cells become dysfunctional in tumor microenvironment (TME) will greatly benefit cancer immunotherapy. We found that increased CD36 expression in tumor-infiltrating CD8(+) T cells, which was induced by TME-cholesterol, was associated with tumor progression and poor survival in human and murine cancers. Genetic ablation of Cd36 in effector CD8(+) T cells exhibited increased cytotoxic cytokine production and enhanced tumor eradication. CD36 mediated uptake of fatty acid by tumor-infiltrating CD8(+) T cells in TME, induced lipid peroxidation and ferroptosis, and led to reduced cytotoxic cytokine production and impaired antitumor ability. Blocking CD36 or inhibiting ferroptosis in CD8(+) T cells effectively restored their antitumor activity and more importantly, possessed greater antitumor efficacy in combination with anti-PD-1 antibodies. This study reveals a new mechanism of CD36 regulating the function of CD8(+) effector T cells and therapeutic potential of targeting CD36 or inhibiting ferroptosis to restore T cell function.